Safety Profile of Methylphenidate Under Long-Term Treatment in Adult ADHD Patients – Results of the COMPAS Study - Kis, Bernhard; Lücke, Caroline; Abdel-Hamid, Mona; Heßmann, Philipp; Graf, Erika; Berger, Mathias; Matthies, Swantje; Borel, Patricia; Sobanski, Esther; Alm, Barbara; Rösler, Michael; Retz, Wolfgang; Jacob, Christian; Colla, Michael; Huss, Michael; Jans, Thomas; van Elst, Ludger Tebartz; Müller, Helge H. O.; Philipsen, Alexandra (Pharmacopsychiatry, 2020)
Introduction The Comparison of Methylphenidate and Psychotherapy in adult ADHD Study (COMPAS) was a prospective, randomized multicenter clinical trial, comparing methylphenidate (MPH) with placebo (PLAC) in combination with cognitive behavioral group psychotherapy (GPT) or individual clinical management (CM) over the period of 1 year. Here, we report results on treatment safety.Methods MPH and PLAC were flexibly dosed. Among 433 randomized patients, adverse events (AEs) were documented and analyzed on an “as received” basis during week 0–52. Electrocardiogram data were recorded at baseline and week 24.Results Comparing 205 patients who received ≥1 dose of MPH with 209 patients who received PLAC, AEs occurring significantly more frequently in the MPH group were decreased appetite (22 vs. 3.8%), dry mouth (15 vs. 4.8%), palpitations (13 vs. 3.3%), gastrointestinal infection (11 vs. 4.8%), agitation (11 vs. 3.3%), restlessness (10 vs. 2.9%), hyperhidrosis, tachycardia, weight decrease (all 6.3 vs. 1.9%), depressive symptom, influenza (both 4.9 vs. 1.0%), and acute tonsillitis (4.4 vs. 0.5%). Syncope occurred significantly more often in the PLAC group (2.4 vs. 0%). Clinically relevant ECG changes occurred very rarely in both groups. Serious AEs were rare and without a significant group difference. The comparison of 206 patients treated with GPT versus 209 patients who received CM revealed no major differences. Serious AE classified as psychiatric occurred in 5 cases in the CM group and in 1 case in the GPT group.Conclusion In this so far longest-running clinical trial, methylphenidate treatment was safe and well-tolerated.
Keywords: Methylphenidate; Adverse events; Adult attention-deficit/hyperactivity disorder; Psychotherapy; Comparison of Methylphenidate and Psychotherapy in adult ADHD Study (COMPAS)